Synthesis, Characterization and Antibacterial Activity of New Chalcones Derived from New Aldehyde; 4-[5-(4`tolyl)-1,3,4-thiadiazole-2-yl] benzaldehyde - Tomma., Jumbad H.; Khazaal, Mustafa S.; Baker, Rajaa K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New chalcones of - - - - y - - hi di z e- -y he y - - e e- - e- - - substituted phenyl have been prepared from condensation of a new of 4-[5-(4`-tolyl)1,3,4-thiadiazole-2-yl] benzaldehyde (which is synthesized by the reaction of 2- amino-5- (4`-tolyl) -1,3,4-thiadiazole and benzaldehyde) with 3- or 4- substituted acetophenones in alkaline medium. The physical, CHNS analysis and spectral data of the synthesized compounds were determined. The biological activity evaluated of new compounds showed that many of these compounds possess antibacterial activity.